Nutritional predictors associated with malnutrition in continuous ambulatory peritoneal dialysis patients. (October 2021) - Hiruy, Aschalew Fikru; Opoku, Sampson; Xiong, Qianqian; Jin, Qiman; Zhao, Jing; Lin, Xuechun; He, Shuiqing; Zuo, Xuezhi; Ying, Chenjiang
Summary: Background: Currently in China, out of the total dialysis population, approximately 20% represents continuous ambulatory peritoneal dialysis (CAPD) and almost half of CAPD patients was affected by malnutrition. This study aimed to investigate the association between nutritional predictors and malnutrition with 5.1 years of dialysis according to the subjective global assessment (SGA) in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: A cross-sectional study was conducted from April 2013 to May 2018 and included 70 CAPD patients. The relationship between anthropometric and biochemical parameters with malnutrition was assessed by multiple logistic regression analysis. Results: The prevalence of malnutrition in CAPD patients was 52.9%. Our result revealed a 7.05-fold increased odds of malnutrition for patients with protein equivalent of total nitrogen appearance normalized to body weight (nPNA) < 1.0 g/kg per day (d) versus patients with normal nPNA (confidence interval (CI) 1.33–37.34; p < 0.05). Patients whose normalized protein catabolic rate (nPCR) was <1.2 g/(kg/d) had a significant positive association with malnutrition versus patients with normal nPCR (adjusted odds ratio (OR) 7.99; p < 0.05). Patients with dietary protein intake (DPI) < 1.0 g/(kg/d) had a higher likelihood of malnutrition than those with normal DPI (OR 12.73; p < 0.05). CAPD patients with upper arm circumference (UAC) < 23.2 cm had a high risk of malnutrition versus patients with normal UAC (OR 12.99; p < 0.05). Conclusions: Our study suggested a close association between nPNA, DPI, nPCR, and UAC and malnutrition in CAPD patients. Further studies can be warranted the use of these variables as predictors and a malnutrition consequence among Chinese CAPD patients.